1981
DOI: 10.1055/s-2007-971670
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antipyretic Activities of Azadirachta indica*

Abstract: The anti-inflammatory and antipyretic activities, as well as the acute toxicity of Azadirachta indica (Neem tree) extract were studied. It was found to have a pronounced anti-inflammatory (rat paw oedema) and a fairly good antipyretic effect (pyrogen induced hyperpyrexia in rabbits). The acute oral toxicity test in mice showed a very low range of approximately 13 g/kg body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 4 publications
2
86
0
1
Order By: Relevance
“…Dietary administration of turmeric was shown to be a potent inhibitor of iron-induced lipid peroxidation [36]. The hepatoprotective, anti-inflammatory, immunomodulatory, and antiulcerogenic effects of neem have been reported during xenobiotic treatment [37][38][39][40]. Of late, there has been considerable interest in the therapeutic ability of neem due to its antioxidant and antimutagenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary administration of turmeric was shown to be a potent inhibitor of iron-induced lipid peroxidation [36]. The hepatoprotective, anti-inflammatory, immunomodulatory, and antiulcerogenic effects of neem have been reported during xenobiotic treatment [37][38][39][40]. Of late, there has been considerable interest in the therapeutic ability of neem due to its antioxidant and antimutagenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…This who used the same decoction from the leaves of guava (P. guajava), paw-paw (C. papaya) lemon grass (C. citratus) and neem tree (A. indica) on chloroquine sensitive strains of Plasmodium berghei in mice. Okpanyi & Ezeukwu (1981) furthered this finding in showing that the extract from the leaves and bark of the above plants had some antipyretic effects. One of the major approaches to the discovery as well as development of new drugs from plants is to study the plants used locally for the treatment of particular ailments.…”
mentioning
confidence: 80%
“…However, the wide ranging medicinal value of the neem leaves stands out in comparison with other parts of the tree. Various studies have indicated that the neem leaves have anti-microbial (Wolinsky et al, 1996;Thakurta et al, 2007;Zhang et al, 2010), anti-inflammatory (Okpanyi and Ezeukwu, 1981;Thoh et al, 2010), analgesic (Khattak et al, 1985), antidiabetic (van der Nat et al, 1991), immunomodulatory (Ray et al, 1996), anti-oxidant (Arivazhagan et al, 2000) and anti-cancer (Miller et al, 1992;Akudugu et al, 2001) properties. Due to its numerous pharmacological activities neem leaves are used as a kaya karpam to promote longevity.…”
Section: Neemmentioning
confidence: 99%